2008
DOI: 10.2340/16501977-0134
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of aquatic and land-based exercise in patients with knee osteoarthritis

Abstract: Only land-based exercise showed some improvement in pain and muscle strength compared with the control group, while no clinical benefits were detectable after aquatic exercise compared with the control group. However, aquatic exercise has significantly less adverse effects compared with a land-based programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
243
7
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 183 publications
(268 citation statements)
references
References 33 publications
9
243
7
9
Order By: Relevance
“…This result differs from what was found by Lund et al 13 , who compared the efficacy of aquatic and non-aquatic exercise programs on the body balance of elderly patients and observed that the aquatic exercises were significantly better for their balance than were the nonaquatic exercises. Nevertheless, it is important to highlight that the subjects of that study suffered from osteoarthritis in their knees, thus differing from our sample.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…This result differs from what was found by Lund et al 13 , who compared the efficacy of aquatic and non-aquatic exercise programs on the body balance of elderly patients and observed that the aquatic exercises were significantly better for their balance than were the nonaquatic exercises. Nevertheless, it is important to highlight that the subjects of that study suffered from osteoarthritis in their knees, thus differing from our sample.…”
Section: Discussioncontrasting
confidence: 56%
“…Likewise, other studies had shown that muscle training has a positive impact on balance among older adults 8,9,11,13,18 . Our training protocol had a frequency of twice a week, for a period of six straight weeks.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations